If it's not what You are looking for type in the equation solver your own equation and let us solve it.
38=-2(z+14)
We move all terms to the left:
38-(-2(z+14))=0
We calculate terms in parentheses: -(-2(z+14)), so:We get rid of parentheses
-2(z+14)
We multiply parentheses
-2z-28
Back to the equation:
-(-2z-28)
2z+28+38=0
We add all the numbers together, and all the variables
2z+66=0
We move all terms containing z to the left, all other terms to the right
2z=-66
z=-66/2
z=-33
| 41-p=23 | | -11=-2x+7 | | -3x+4-2x=-5x+10 | | 3x–24=–6 | | 4(-5j+9)=-4+220 | | G(2)=2²+7x-3 | | 6x2(x-5)=46 | | 5x+3x+4=6x+20 | | 35n=10n | | 21.8=6.9+z | | -100=5(z+14) | | –2j=–j+9 | | 2x+4=-3x-16 | | 4x-3=5+-3x | | f/1.5=-4.3 | | 4(-x-1.6)=-4x-6.4 | | x-(15=12) | | 12x-(-6)=4212x=48x=4 | | 6(x+3)+2x=14 | | 1.5w+5=3+2w | | 2(4x+2)-3=8x+-1 | | 12x-(-6)=4212x=48x=4* | | 3x^2-26=-48 | | 2(8n)=96 | | 4(5y−8−2)=160 | | 16n^2-72n+54=-2 | | 4-(1-7u)1/3=0 | | 20+3*x=131 | | Y=-9x+500 | | 5(2n+8)+3=-33 | | -18=z-(-14) | | 7x-56+11x=48 |